Upper Gastrointestinal Bleeding as a Manifestation of Metastasis from Laryngeal Cancer. Issue 3 (April 2015) - Singh, Amandeep; Nazeer, Hammad; Thakur, Kshitij; Zeitz, Monica
Abstract : N/A: Upper gastrointestinal (GI) bleeding can be a rare manifestation of primary or metastatic tumor in the stomach. Tumors that commonly metastasize to stomach include breast, lung, and malignant melanoma. Laryngeal cancer usually metastasizes to the lung and cervical spine. We report the first case of upper GI bleed as a manifestation of laryngeal cancer in the stomach.